The wars for Asia, 1911-1949 - Paine, S. C. M., 1957- (Cambridge University Press, 2012)
The Wars for Asia, 1911-1949 shows that the Western treatment of World War II, the Second Sino-Japanese War, and the Chinese Civil War as separate events misrepresents their overlapping connections and causes. The long Chinese Civil War precipitated a long regional war between China and Japan that went global in 1941 when the Chinese found themselves fighting a civil war within a regional war within an overarching global war. The global war that consumed Western attentions resulted from Japan's peripheral strategy to cut foreign aid to China by attacking Pearl Harbor and Western interests throughout the Pacific on December 7-8, 1941. S. C. M. Paine emphasizes the fears and ambitions of Japan, China and Russia, and the pivotal decisions that set them on a collision course in the 1920s and 1930s. The resulting wars, the Chinese Civil War (1911-1949), the Second Sino-Japanese War (1931-1945) and World War II (1939-1945), together yielded a viscerally anti-Japanese and unified Communist China, the still-angry rising power of the early twenty-first century. While these events are history in the West, they live on in Japan and especially China.